INTEGRASI ETNIS INDIA PASCA PENETAPAN KEBIJAKAN 1MALAYSIA POLICY - Muslimah, Siti; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The diversity of Malaysian society which consists of Malay race, Chinese and India has a myriad of policies that make the country engaged in racial conflict. In 1971, Tun Abd Razak submit proposals regarding economic policy that NEP (New Economy Programme). The policy aims to protect the ethnic Malay. It was based on concerns raised that the residents are ethnic Chinese and Indians at the time had a better life than the residents are ethnic Malays. The condition is feared to turn off citizens to ethnic Malays, these policies have been positive discrimination a form of affirmative action policies designed to rectify the shortcomings of a group.One of the main objectives in the process of nation building in Malaysia is the formation of national identity, which previously no single identity that unites the various ethnic groups in Malaysia. Then development the Malaysian government thinking to make a policy formula to unite the community in strengthening the country in facing globalization for the sake of national achievement. In 2010, the Malaysian government has a new policy in the know with the policy of One Malaysia. This study aims to reveal how Integratin Of Ethnic Indian After The Determination Of 1Malaysia Policy. The reality of the existence of the theory of constructivism researchers used the National Integration Theory of Ethnicity and Nation State and National-Building concept in the process of this thesis research. Mechanical research is interview and direct observation by researchers.The results showed the Process Of Integration Of Ethnic Indians After The Determinationt Of 1Malaysia Policy has not gone well. Still there are some forms of discrimination against ethnic Indians in which the government is legally legalize discrimination.Keywords: Integration, Ethnicity, National Building, 1Malaysia Policy, Discrimination.